What Makes a Blog a Blog? Exploring User Conceptualizations of an Old “New” Online Medium - Treem, Jeffrey; Thomas, Kristin (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
What is a blog? While this may seem like a basic question, it is the subject of dispute among researchers, and hardly settled among users of the medium. We return to this fundamental inquiry by asking 89 blog-reading college students how they conceptualize the term and what purpose blogs serve for them. Our findings suggest that perceptions of blogs are varied and ambiguous, and definitions largely fail to distinguish blogs from other online media. We discuss what this means for the study of blogs and other “new” media and argue that more constructionist approaches are necessary to develop ecologically valid theories of media perceptions and use.